Improved conductivity in tape casted Li-NASICON supported thick films: Effect of temperature treatments and lamination. Issue 4 (April 2018) - Jiménez, R.; del Campo, A.; Calzada, M.L.; Sanz, J.; Kobylianska, S.D.; Liniova, B.O.; Belous, A.G.; Ragulya, А.V.
Abstract: In this work, the influence of different thermal sintering treatments on Li1.3 Al0.3 Ti1.7 (PO4 )3 NASICON thick films has been investigated. The isostatic lamination step performed before the thermal sintering of thick films has demonstrated to improve film density and grain size, increasing "bulk" and grain boundary Li-conductivities. The confocal Raman spectroscopy characterization allowed the observation of the connectivity of the particles present in the ceramic samples and so a deeper understanding of ionic conductivity. The dependence of total and "bulk" Li conductivity on the samples microstructure is discussed. The films sintered by slow heating sintering with a previous lamination step, displayed an overall Li- conductivity >10 −4 Ω -1 cm -1, that is superior to that reported in commercial OHARA Li- NASICON glass ceramics. The tape casting deposition method is scalable for preparation of large area thick supported electrolyte films with high conductivity for novel Li ion all solid state batteries (ASSB) architectures.